(untitled) (Journal of actual problems of jurisprudence, 2019)
In given article the sense and value of terms "debt" and "duty" in the text of the Constitution is defined and becomes всесторонниий the analysis of the same concepts. Importance of use of different forms of one concept Is underlined at formation of legal consciousness of people.